Accuracy of trabecular structure by HR-pQCT compared to gold standard ?CT in the radius and tibia of patients with osteoporosis and long-term bisphosphonate therapy - Krause, M.; Museyko, Oleg; Breer, S.; Wulff, B.; Duckstein, C.; Vettorazzi, Eik; Glueer, C.; Pueschel, K.; Engelke, Klaus; Amling, M. (Osteoporosis international, 2014)
Despite an increasing use of high-resolution peripheral quantitative computed tomography (HR-pQCT) to evaluate bone morphology in vivo, there are reservations about its applicability in patients with osteoporosis and antiresorptive therapy. This study shows that HR-pQCT provides acceptable in vivo accuracy for bone volume fraction (BV/TV) in patients with osteoporosis and bisphosphonate (BP) treatment.The primary aim was to analyze agreement of trabecular structure between HR-pQCT and gold standard microtomography (?CT) in patients with osteoporosis and long-term BP therapy.In the BioAsset study, we analyzed cadaver radii and tibiae of 34 postmenopausal females (81.1 ± 7.1 years) with osteoporosis (no BP n = 22, 1-5 years BP n = 5, >5 years BP n = 7). Two HR-pQCT protocols (patient-mode and ?CT-mode) were compared with gold standard ?CT after image registration. Undecalcified histological sections were obtained to quantify nonmineralized bone matrix. Bland-Altman plots illustrated methodological agreement. Multiple regression analysis was used to test for variables associated with method agreement.In the radius and tibia, patient-mode HR-pQCT derived indices including bone volume fraction, trabecular number, and trabecular separation correlated well with gold standard ?CT (R(2) = 0.78 - 0.88) except for trabecular thickness (R(2) = 0.11). Bland-Altman plots illustrated adequate agreement for bone volume fraction. Lower agreement of trabecular number and trabecular separation improved with decreasing structural impairment at the tibia only. Trabecular thickness was not appropriately assessed with HR-pQCT at both skeletal sites. Higher agreement for bone volume fraction was associated with increasing tissue mineral density in the tibia.HR-pQCT provides acceptable in vivo accuracy for BV/TV in patients with osteoporosis and BP treatment. Higher TMD was associated with higher BV/TV accuracy in vivo. Overall, methodological agreement got less accurate with increasing structural impairment in the tibia.
EVALuna2:10096

A COMPARISON OF TWO METHODS TO SEGMENT BONE EROSIONS IN THE METACARPOPHALANGEAL JOINTS OF RHEUMATOID ARTHRITIS PATIENTS - Figueiredo, C.; Simon, David; Stemmler, F.; Weißenfels, Anja; Weishäupl, Dirk; Museyko, Oleg; Friedberger, Andreas; Rech, Jürgen; Hueber, Axel; Haschka, J.; Schett, Georg; Engelke, Klaus; et al. (2016)
EVALuna2:13471

ADVANCED 3D REGISTRATION FOR MONITORING PERIPHERAL BMD AND BMC CHANGES IN GROWING BONES IN CHILDREN - Friedberger, Andreas; Museyko, Oleg; Genant, H. H.; Engelke, Klaus (2018)
EVALuna2:36401

Advanced Knee Structure Analysis (AKSA): a comparison of bone mineral density and trabecular texture measurements using computed tomography and high-resolution peripheral quantitative computed tomography of human knee cadavers - Lowitz, Torsten; Museyko, Oleg; Bousson, Valerie; Chappard, Christine; Laouisset, Liess; Laredo, Jean-Denis; Engelke, Klaus (Arthritis Research & Therapy, 2017)
BACKGROUND: A change of loading conditions in the knee causes changes in the subchondral bone and may be a cause of osteoarthritis (OA). However, quantification of trabecular architecture in vivo is difficult due to the limiting spatial resolution of the imaging equipment; one approach is the use of texture parameters. In previous studies, we have used digital models to simulate changes of subchondral bone architecture under OA progression. One major result was that, using computed tomography (CT) images, subchondral bone mineral density (BMD) in combination with anisotropy and global homogeneity could characterize this progression. The primary goal of this study was a comparison of BMD, entropy, anisotropy, variogram slope, and local and global inhomogeneity measurements between high-resolution peripheral quantitative CT (HR-pQCT) and CT using human cadaveric knees. The secondary goal was the verification of the spatial resolution dependence of texture parameters observed in the earlier simulations, two important prerequisites for the interpretation of in vivo measurements in OA patients. METHOD: The applicability of texture analysis to characterize bone architecture in clinical CT examinations was investigated and compared to results obtained from HR-pQCT. Fifty-seven human knee cadavers (OA status unknown) were examined with both imaging modalities. Three-dimensional (3D) segmentation and registration processes, together with automatic positioning of 3D analysis volumes of interest (VOIs), ensured the measurement of BMD and texture parameters at the same anatomical locations in CT and HR-pQCT datasets. RESULTS: According to the calculation of dice ratios (>0.978), the accuracy of VOI locations between methods was excellent. Entropy, anisotropy, and global inhomogeneity showed significant and high linear correlation between both methods (0.68 < R2 < 1.00). The resolution dependence of these parameters simulated earlier was confirmed by the in vitro measurements. CONCLUSION: The high correlation of HR-pQCT- and CT-based measurements of entropy, global inhomogeneity, and anisotropy suggests interchangeability between devices regarding the quantification of texture. The agreement of the experimentally determined resolution dependence of global inhomogeneity and anisotropy with earlier simulations is an important milestone towards their use to quantify subchondral bone structure. However, an in vivo study is still required to establish their clinical relevance.
EVALuna2:33267

A low-radiation exposure protocol for 3D QCT of the spine - Museyko, Oleg; Heinemann, A.; Krause, M.; Wulff, B.; Amling, M.; Pueschel, K.; Glueer, C. C.; Kalender, Willi Alfred; Engelke, Klaus (Osteoporosis international, 2014)
Cadaver and phantom measurements and simulations confirmed that radiation exposure in 3D QCT of the spine can be reduced if 80 kV instead of 120 kV protocols are used; 120 mAs and slice thicknesses of 1-1.3 mm should be usable but obese patient will require higher milliampere-second settings.To develop a low-radiation exposure CT acquisition protocol for 3D QCT of the thoracolumbar spine.Twenty-six cadavers were scanned with a standard protocol of 120 kV, 100 mAs and with a low-dose protocol using 90 kV, 150 mAs. The scan range included the vertebrae T6 to L4. Each vertebra was segmented and the integral volume and BMD of the total vertebral body were determined. Effective dose values were estimated. The impact of milliampere-second reduction on image quality was simulated by adding noise.One hundred ninety-six vertebrae were analyzed. Integral volume as well as integral BMD correlated significantly (p < 0.001) between standard and low-dose protocols (volume, r (2) = 0.991, residual root mean square (RMS) error, 0.77 cm(3); BMD, r (2) = 0.985, RMS error, 4.21 mg/cm(3)). The slope significantly differed from 1 for integral BMD but not for volume hinting at residual field inhomogeneity differences between the two voltage settings that could be corrected by cross-calibration. Compared to the standard protocol, effective dose was reduced by over 50 % in the low-dose protocol. Adding noise in the 90 kV images to simulate a reduction from 150 to 100 mAs did not affect the results for integral volume or BMD.For 3D QCT of the spine, depending on scanner type, 80 or 90 kV instead of 120 kV protocols may be considered as an important option to reduce radiation exposure; 120 mAs and slice thicknesses of 1-1.5 mm are usable if segmentation is robust to noise. In obese patients, higher milliampere-second settings will be required.
EVALuna2:10069

A new CT based approach to quantify adipose tissue in paraspinal muscle - Engelke, Klaus; Museyko, Oleg; Guenzel, Daniel; Maier, Andreas; Laredo, Jean-Denis (2018)
EVALuna2:36396

A NEW METHOD FOR THE QUANTITATIVE ANALYSIS OF HAND MUSCLE VOLUME FOR PATIENTS WITH RHEUMATOID ARTHRITIS - Friedberger, Andreas; Museyko, Oleg; Figueiredo, C.; Bäuerle, Tobias; Chaudry, Oliver; Grimm, Alexandra; Schett, Georg; Engelke, Klaus (2016)
EVALuna2:13491

A new method to determine cortical bone thickness in CT images using a hybrid approach of parametric profile representation and local adaptive thresholds: Accuracy results - Museyko, Oleg; Gerner, Bastian; Engelke, Klaus (PLoS ONE, 2017)
MOTIVATION: Cortical bone is an important contributor to bone strength and is pivotal to understand the etiology of osteoporotic fractures and the specific mechanisms of antiosteoporotic treatment regimen. 3D computed tomography (CT) can be used to measure cortical thickness, density, and mass in the proximal femur, lumbar vertebrae, and distal forearm. However, the spatial resolution of clinical whole body CT scanners is limited by radiation exposure; partial volume artefacts severely impair the accurate assessment of cortical parameters, in particular in locations where the cortex is thin such as in the lumbar vertebral bodies or in the femoral neck. METHOD: Model-based deconvolution approaches recover the cortical thickness by numerically deconvolving the image along 1D profiles using an estimated scanner point spread function (PSF) and a hypothesized uniform cortical bone mineral density (reference density). In this work we provide a new essentially analytical unique solution to the model-based cortex recovery problem using few characteristics of the measured profile and thus eliminate the non-linear optimization step for deconvolution. Also, the proposed approach allows to get rid of the PSF in the model and reduces sensitivity to errors in the reference density. Additionally, run-time and memory effective computation of cortical thickness was achieved with the help of a lookup table. RESULTS: The method accuracy and robustness was validated and compared to that of a deconvolution approach recently proposed for cortical bone and of the 50% relative threshold technique: in a simulated environment with noise and various error levels in the reference density and using CT acquisitions of the European Forearm Phantom (EFP II), a modification of a widely used anthropomorphic standard of cortical and trabecular bone compartments that was scanned with various scan protocols. CONCLUSION: Results of simulations and of phantom data analysis verified the following properties of the new method: 1) Robustness against errors in the reference density. 2) Excellent accuracy on ground truth data with various noise levels. 3) Very fast computation using a lookup table.
EVALuna2:33264

A reproducible semi-automatic method to quantify the muscle-lipid distribution in clinical 3D CT images of the thigh - Mühlberg, Alexander; Museyko, Oleg; Laredo, Jean-Denis; Engelke, Klaus (PLoS ONE, 2017)
Many studies use threshold-based techniques to assess in vivo the muscle, bone and adipose tissue distribution of the legs using computed tomography (CT) imaging. More advanced techniques divide the legs into subcutaneous adipose tissue (SAT), anatomical muscle (muscle tissue and adipocytes within the muscle border) and intra- and perimuscular adipose tissue. In addition, a so-called muscle density directly derived from the CT-values is often measured. We introduce a new integrated approach to quantify the muscle-lipid system (MLS) using quantitative CT in patients with sarcopenia or osteoporosis. The analysis targets the thigh as many CT studies of the hip do not include entire legs The framework consists of an anatomic coordinate system, allowing delineation of reproducible volumes of interest, a robust semi-automatic 3D segmentation of the fascia and a comprehensive method to quantify of the muscle and lipid distribution within the fascia. CT density-dependent features are calibrated using subject-specific internal CT values of the SAT and external CT values of an in scan calibration phantom. Robustness of the framework with respect to operator interaction, image noise and calibration was evaluated. Specifically, the impact of inter- and intra-operator reanalysis precision and addition of Gaussian noise to simulate lower radiation exposure on muscle and AT volumes, muscle density and 3D texture features quantifying MLS within the fascia, were analyzed. Existing data of 25 subjects (age: 75.6 ± 8.7) with porous and low-contrast muscle structures were included in the analysis. Intra- and inter-operator reanalysis precision errors were below 1% and mostly comparable to 1% of cohort variation of the corresponding features. Doubling the noise changed most 3D texture features by up to 15% of the cohort variation but did not affect density and volume measurements. The application of the novel technique is easy with acceptable processing time. It can thus be employed for a comprehensive quantification of the muscle-lipid system enabling radiomics approaches to musculoskeletal disorders.
EVALuna2:33265

Automated three-dimensional registration of high-resolution peripheral quantitative computed tomography data to quantify size and shape changes of arthritic bone erosions - Toepfer, Dominique; Gerner, Bastian; Finzel, Stephanie; Kraus, Sebastian; Museyko, Oleg; Schett, Georg; Engelke, Klaus (Rheumatology, 2015)
To monitor size and shape changes of bone erosions and changes in BMD in the vicinity of the erosion and in the periarticular trabecular compartment of patients with RA using high-resolution peripheral quantitative CT (HR-pQCT) imaging and to compare an automated three-dimensional (3D) image processing technique with manual measurements of erosion width and depth.The shape of 40 bone erosions and composition of bone around the erosions were analysed in the MCP joints of 22 RA patients both manually and by semi-automated 3D image processing at two different time points. Periosteal segmentation was performed using volume growing and morphological operations. Image registration was applied for transfer of baseline segmentations to follow-up datasets.Eight erosions decreased in size, 6 increased and 28 remained stable. Increasing erosions were more spherical and smaller at baseline compared with decreasing or stable erosions. BMD in the vicinity of shrinking erosions increased, while it decreased next to expanding erosions. There was moderate agreement in the determination of erosion volume between semi-automated and manual measurements, but agreement was poor when assessing changes in volume over time.Longitudinal changes in erosion size and shape and of BMD in the vicinity of an erosion can be measured. BMD changes are associated with progression and regression of erosions. However, the semi-automated and manual approaches did not classify longitudinal changes of erosion volume in the same way. Further research is necessary to define the nature of these differences.
EVALuna2:10105

Characterization and quantification of angiogenesis in rheumatoid arthritis in a mouse model using ?CT - Gayetskyy, Svitlana; Museyko, Oleg; Käßer, Johannes; Heß, Andreas; Schett, Georg; Engelke, Klaus (BMC Musculoskeletal Disorders, 2014)
Angiogenesis is an important pathophysiological process of chronic inflammation, especially in inflammatory arthritis. Quantitative measurement of changes in vascularization may improve the diagnosis and monitoring of arthritis. The aim of this work is the development of a 3D imaging and analysis framework for quantification of vascularization in experimental arthritis.High-resolution micro-computed tomography (?CT) was used to scan knee joints of arthritic human tumor necrosis factor transgenic (hTNFtg) mice and non-arthritic wild-type controls previously perfused with lead-containing contrast agent Microfil MV-122. Vessel segmentation was performed by combination of intensity-based (local adaptive thresholding) and form-based (multi-scale method) segmentation techniques. Four anatomically defined concentric spherical shells centered in the knee joint were used as analysis volumes of interest. Vessel density, density distribution as well as vessel thickness, surface, spacing and number were measured. Simulated digital vessel tree models were used for validation of the algorithms.High-resolution ?CT allows the quantitative assessment of the vascular tree in the knee joint during arthritis. Segmentation and analysis were highly automated but occasionally required manual corrections of the vessel segmentation close to the bone surfaces. Vascularization was significantly increased in arthritic hTNFtg mice compared to wild type controls. Precision errors for the morphologic parameters were smaller than 3% and 6% for intra- and interoperator analysis, respectively. Accuracy errors for vessel thickness were around 20% for vessels larger than twice the resolution of the scanner.Arthritis-induced changes of the vascular tree, including detailed and quantitative description of the number of vessel branches, length of vessel segments and the bifurcation angle, can be detected by contrast-enhanced high-resolution ?CT.
EVALuna2:8512

Comparison of proximal femur and vertebral body strength improvements in the FREEDOM trial using an alternative finite element methodology - Zysset, Philippe; Pahr, Dieter; Engelke, Klaus; Genant, Harry K.; Mcclung, Michael R.; Kendler, David L.; Recknor, Christopher; Kinzl, Michael; Schwiedrzik, Jakob; Museyko, Oleg; Wang, Andrea; Libanati, Cesar (Bone, 2015)
Denosumab reduced the incidence of new fractures in postmenopausal women with osteoporosis by 68% at the spine and 40% at the hip over 36months compared with placebo in the FREEDOM study. This efficacy was supported by improvements from baseline in vertebral (18.2%) strength in axial compression and femoral (8.6%) strength in sideways fall configuration at 36months, estimated in Newtons by an established voxel-based finite element (FE) methodology. Since FE analyses rely on the choice of meshes, material properties, and boundary conditions, the aim of this study was to independently confirm and compare the effects of denosumab on vertebral and femoral strength during the FREEDOM trial using an alternative smooth FE methodology. Unlike the previous FE study, effects on femoral strength in physiological stance configuration were also examined. QCT data for the proximal femur and two lumbar vertebrae were analyzed by smooth FE methodology at baseline, 12, 24, and 36months for 51 treated (denosumab) and 47 control (placebo) subjects. QCT images were segmented and converted into smooth FE models to compute bone strength. L1 and L2 vertebral bodies were virtually loaded in axial compression and the proximal femora in both fall and stance configurations. Denosumab increased vertebral body strength by 10.8%, 14.0%, and 17.4% from baseline at 12, 24, and 36months, respectively (p<0.0001). Denosumab also increased femoral strength in the fall configuration by 4.3%, 5.1%, and 7.2% from baseline at 12, 24, and 36months, respectively (p<0.0001). Similar improvements were observed in the stance configuration with increases of 4.2%, 5.2%, and 5.2% from baseline (p<=0.0007). Differences between the increasing strengths with denosumab and the decreasing strengths with placebo were significant starting at 12months (vertebral and femoral fall) or 24months (femoral stance). Using an alternative smooth FE methodology, we confirmed the significant improvements in vertebral body and proximal femur strength previously observed with denosumab. Estimated increases in strength with denosumab and decreases with placebo were highly consistent between both FE techniques.
EVALuna2:10112

Methods for segmentation of rheumatoid arthritis bone erosions in high-resolution peripheral quantitative computed tomography (HR-pQCT) - Figueiredo, Camille P.; Kleyer, Arnd; Simon, Dominic; Stemmler, Fabian; d'Oliveira, Isabelle; Weißenfels, Anja; Museyko, Oleg; Friedberger, Andreas; Hueber, Axel; Haschka, Judith; Englbrecht, Matthias; Pereira, Rosa M.R.; et al. (Seminars in Arthritis and Rheumatism, 2017)
The comparison between different techniques to quantify the 3-dimensional size of inflammatory bone erosions in rheumatoid arthritis(RA) patients.Anti-cyclic citrullinated peptide antibody(ACPA) positive RA patients received high-resolution peripheral quantitative computed tomography (HR-pQCT) scans of the metacarpophalangeal joints (MCP). Erosions were measured by three different segmentation techniques: (1) manual method with calculation by half-ellipsoid formula, (2) semi-automated modified Evaluation Script for Erosions (mESE), and (3) semi-automated Medical Image Analysis Framework (MIAF) software. Bland & Altman plots were used to describe agreement between methods. Furthermore, shape of erosions was classified as regular or irregular and then compared to the sphericity obtained by MIAF.A total of 76 erosions from 65 RA patients (46 females/19 males), median age 57 years, median disease duration 6.1 years and median disease activity score 28 of 2.8 units were analyzed. While mESE and MIAF showed good agreement in the measurement of erosion size, the manual method with calculation by half-ellipsoid formula underestimated erosions size, particularly with larger erosions. Accurate segmentation is particularly important in larger erosions, which are irregularly shaped. In all three segmentation techniques irregular erosions were larger in size than regular erosions (MIAF: 19.7 vs. 3.4mm(3); mESE: 15.5 vs. 2.3mm(3); manual = 7.2 vs. 1.52mm(3); all p < 0.001). In accordance, sphericity of erosions measured by MIAF significantly decreased with their size (p < 0.001).MIAF and mESE allow segmentation of inflammatory bone erosions in RA patients with excellent inter reader reliability. They allow calculating erosion volume independent of erosion shape and therefore provide an attractive tool to quantify structural damage in individual joints of RA patients.
EVALuna2:13514

On the Application of the Monge-Kantorovich Problem to Image Registration - Museyko, Oleg; Stiglmayr, Michael; Klamroth, Kathrin; Leugering, Günter (Siam Journal on Imaging Sciences, 2009)
A problem of image registration is considered in the context of optimal mass transportation. The properties and limitations of an optimal image transportation are analyzed. A modified formulation of this approach is proposed in order to overcome the morphing effect. Finally, a fast and simple scale-space approach for the new formulation is introduced, and numerical examples are presented.
Keywords: image registration; image morphing; optimal mass transportation; Monge-Kantorovich problem; 94A08; 92C55; 49N99

Prediction of Hip Failure Load: In Vitro Study of 80 Femurs Using Three Imaging Methods and Finite Element Models-The European Fracture Study (EFFECT) - Pottecher, Pierre; Engelke, Klaus; Duchemin, Laure; Museyko, Oleg; Moser, Thomas; Mitton, David; Vicaut, Eric; Adams, Judith; Skalli, Wafa; Laredo, Jean Denis; Bousson, Valerie (Radiology, 2016)
Purpose To evaluate the performance of three imaging methods (radiography, dual-energy x-ray absorptiometry [DXA], and quantitative computed tomography [CT]) and that of a numerical analysis with finite element modeling (FEM) in the prediction of failure load of the proximal femur and to identify the best densitometric or geometric predictors of hip failure load. Materials and Methods Institutional review board approval was obtained. A total of 40 pairs of excised cadaver femurs (mean patient age at time of death, 82 years ± 12 [standard deviation]) were examined with (a) radiography to measure geometric parameters (lengths, angles, and cortical thicknesses), (b) DXA (reference standard) to determine areal bone mineral densities (BMDs), and (c) quantitative CT with dedicated three-dimensional analysis software to determine volumetric BMDs and geometric parameters (neck axis length, cortical thicknesses, volumes, and moments of inertia), and (d) quantitative CT-based FEM to calculate a numerical value of failure load. The 80 femurs were fractured via mechanical testing, with random assignment of one femur from each pair to the single-limb stance configuration (hereafter, stance configuration) and assignment of the paired femur to the sideways fall configuration (hereafter, side configuration). Descriptive statistics, univariate correlations, and stepwise regression models were obtained for each imaging method and for FEM to enable us to predict failure load in both configurations. Results Statistics reported are for stance and side configurations, respectively. For radiography, the strongest correlation with mechanical failure load was obtained by using a geometric parameter combined with a cortical thickness (r(2) = 0.66, P < .001; r(2) = 0.65, P < .001). For DXA, the strongest correlation with mechanical failure load was obtained by using total BMD (r(2) = 0.73, P < .001) and trochanteric BMD (r(2) = 0.80, P < .001). For quantitative CT, in both configurations, the best model combined volumetric BMD and a moment of inertia (r(2) = 0.78, P < .001; r(2) = 0.85, P < .001). FEM explained 87% (P < .001) and 83% (P < .001) of bone strength, respectively. By combining (a) radiography and DXA and (b) quantitative CT and DXA, correlations with mechanical failure load increased to 0.82 (P < .001) and 0.84 (P < .001), respectively, for radiography and DXA and to 0.80 (P < .001) and 0.86 (P < .001) , respectively, for quantitative CT and DXA. Conclusion Quantitative CT-based FEM was the best method with which to predict the experimental failure load; however, combining quantitative CT and DXA yielded a performance as good as that attained with FEM. The quantitative CT DXA combination may be easier to use in fracture prediction, provided standardized software is developed. These findings also highlight the major influence on femoral failure load, particularly in the trochanteric region, of a densitometric parameter combined with a geometric parameter. (©) RSNA, 2016 Online supplemental material is available for this article.
EVALuna2:33284

QCT of the femur: Comparison between QCTPro and MIAF Femur - Wang, Ling; Museyko, Oleg; Engelke, Klaus; Brown, Keenan; Cheng, Xiaoguang (2018)
EVALuna2:36394

QCT of the femur: Comparison between QCTPro CTXA and MIAF Femur - Wang, Ling; Museyko, Oleg; Su, Yongbin; Brown, Keenan; Yang, Ruopei; Zhang, Yong; Duanmu, Yangyang; Guo, Zhe; Zhang, Wei; Yan, Dong; Cheng, Xiaoguang; Engelke, Klaus (Bone, 2019)
QCT is commonly employed in research studies and clinical trials to measure BMD at the proximal femur. In this study we compared two analysis software options, QCTPro CTXA and MIAF-Femur, using CT scans of the semi-anthropometric European Proximal Femur Phantom (EPFP) and in vivo data from 130 Chinese elderly men and women aged 60-80 years.
CRIS-Team WoS Importer:2019-02-27

QCT of the proximal femur–which parameters should be measured to discriminate hip fracture? - Museyko, Oleg; Bousson, V.; Adams, J.; Laredo, J. -D.; Engelke, Klaus (Osteoporosis international, 2016)
SUMMARY: For quantitative computed tomography (QCT), most relevant variables to discriminate hip fractures were determined. A multivariate analysis showed that trabecular bone mineral density (BMD) of the trochanter with "cortical" thickness of the neck provided better fracture discrimination than total hip integral BMD. A slice-by-slice analysis of the neck or the inclusion of strength-based parameters did not improve fracture discrimination. INTRODUCTION: For QCT of the proximal femur, a large variety of analysis parameters describing bone mineral density, geometry, or strength has been considered. However, in each given study, generally just a small subset was used. The aim of this study was to start with a comprehensive set and then select a best subset of QCT parameters for discrimination of subjects with and without acute osteoporotic hip fractures. METHODS: The analysis was performed using the population of the European Femur Fracture (EFFECT) study (Bousson et al. J Bone Min Res: Off J Am Soc Bone Min Res 26:881-893, 2011). Fifty-six female control subjects (age 73.2 ± 9.3 years) were compared with 46 female patients (age 80.9 ± 11.1 years) with acute hip fractures. The QCT analysis software MIAF-Femur was used to virtually dissect the proximal femur and analyze more than 1000 parameters, predominantly in the femoral neck. A multivariate best-subset analysis was used to extract the parameters best discriminating hip fractures. All results were adjusted for age, height, and weight differences between the two groups. RESULTS: For the discrimination of all proximal hip fractures as well as for cervical fractures alone, the measurement of neck parameters suffices (area under the curve (AUC) = 0.84). Parameters characterizing bone strength are discriminators of hip fractures; however, in multivariate models, only "cortical" cross-sectional area in the neck center remained as a significant contributor. The combination of one BMD parameter, trabecular BMD of the trochanter, and one geometry parameter, "cortical" thickness of the neck discriminated hip fracture with an AUC value of 0.83 which was significantly better than 0.77 for total femur BMD alone. A comprehensive slice-based analysis of the neck along its axis did not significantly improve hip fracture discrimination. CONCLUSIONS: If QCT of the hip is performed, the analysis should include neck and trochanter. In particular, for fractures of any type, a comprehensive slice-based analysis of the neck along its axis did not significantly improve hip fracture discrimination nor did the inclusion of strength-related parameters other than "cortical" area or thickness. One BMD and one geometry parameter, in this study, the combination of trabecular BMD of the trochanter and of "cortical" thickness of the neck resulted in significant hip fracture discrimination.
EVALuna2:33285

Quantitative analysis of skeletal muscle by computed tomography imaging-State of the art - Engelke, Klaus; Museyko, Oleg; Wang, Ling; Laredo, Jean-Denis (Journal of Orthopaedic Translation, 2018)
The radiological assessment of muscle properties-size, mass, density (also termed radiodensity), composition, and adipose tissue infiltration-is fundamental in muscle diseases. More recently, it also became obvious that muscle atrophy, also termed muscle wasting, is caused by or associated with many other diseases or conditions, such as inactivity, malnutrition, chronic obstructive pulmonary disorder, cancer-associated cachexia, diabetes, renal and cardiac failure, and sarcopenia and even potentially with osteoporotic hip fracture. Several techniques have been developed to quantify muscle morphology and function. This review is dedicated to quantitative computed tomography (CT) of skeletal muscle and only includes a brief comparison with magnetic resonance imaging. Strengths and limitations of CT techniques are discussed in detail, including CT scanner calibration, acquisition and reconstruction protocols, and the various quantitative parameters that can be measured with CT, starting from simple volume measures to advanced parameters describing the adipose tissue distribution within muscle. Finally, the use of CT in sarcopenia and cachexia and the relevance of muscle parameters for the assessment of osteoporotic fracture illustrate the application of CT in two emerging areas of medical interest.
EVALuna2:36397

QUANTITATIVE ASSESSMENT AND ANALYSIS OF HAND MUSCLE VOLUME - Friedberger, Andreas; Figueiredo, C.; Museyko, Oleg; Grimm, Alexandra; D'Oliveira, I.; Bäuerle, Tobias; Rech, Jürgen; Chaudry, Oliver; Uder, Michael; Schett, Georg; Engelke, Klaus (2017)
EVALuna2:14726

Segmentation and quantification of bone erosions in high-resolution peripheral quantitative computed tomography datasets of the metacarpophalangeal joints of patients with rheumatoid arthritis - Toepfer, Dominique; Finzel, Stephanie; Museyko, Oleg; Schett, Georg; Engelke, Klaus (Rheumatology, 2014)
Objective. To develop a precise three-dimensional (3D) segmentation technique for bone erosions in high-resolution peripheral quantitative CT (HR-pQCT) datasets to measure their volume, surface area and shape parameters. Assessment of bone erosions in patients with RA is important for diagnosis and evaluation of treatment efficacy. HR-pQCT allows quantifying periarticular bone loss in arthritis. Methods. HR-pQCT scans with a spatial resolution of about 120 µm of the second to fourth metacarpophalangeal joints were acquired in patients with RA. Erosions were identified by placing a seed point in each of them. After applying 3D segmentation, the volume, surface area and sphericity of erosions were calculated. Results were compared with an approximation method using manual measurements. Intra- and interoperator precision analysis was performed for both the 3D segmentation and the manual technique. Results. Forty-three erosions were assessed in 18 datasets. Intra- and interoperator precisions (RMSCV/RMSSD) for erosion volume were 5.66%/0.49 mm(3) and 7.76%/0.76 mm(3), respectively. The correlation between manual measurements and their simulation using segmentation volumes was r = 0.87. Precision errors for the manual method were 15.39% and 0.36 mm(3), respectively. Conclusion. We developed a new precise 3D segmentation technique for quantification of bone erosions in HR-pQCT datasets that correlates to the volume, shape and surface area of the erosion. The technique allows fast and effective measurement of the erosion size and could therefore be helpful for rapid and quantitative assessment of erosion size.
EVALuna2:10057

THREE DIMENSIONAL COMPARISONS BETWEEN QCTPRO AND MIAF FEMUR FOR THE PROXIMAL FEMUR MEASUREMENTS - Wang, L.; Museyko, Oleg; Brown, K.; Cheng, X.; Engelke, Klaus (2018)
EVALuna2:36402

Three-dimensional Distribution of Muscle and Adipose Tissue of the Thigh at CT: Association with Acute Hip Fracture - Mühlberg, Alexander; Museyko, Oleg; Bousson, Vallrie; Pottecher, Pierre; Laredo, Jean-Denis; Engelke, Klaus (Radiology, 2019)
Purpose: To evaluate determinants of hip fracture by assessing soft-tissue composition of the upper thigh at CT.
CRIS-Team WoS Importer:2019-02-21